Crashworthiness and Failure Mechanism of Polylactic Acid Multi-Cell Tubes Hybridized with Aluminum/Copper Under Axial Compression - Muhammad Syaiful Fadly; Khairil Anwar; Muhammad Sadat Hamzah; I Komang Diego Antara (Universitas Muhammadiyah Magelang, 2026)
This research investigates the crashworthiness performance and energy absorption behavior of crash boxes constructed from hybrid materials comprising Polylactic acid (PLA), aluminum (Al), and copper (Cu) under quasi-static axial compression. The crash box configuration comprises a PLA outer shell, an internal Al or Cu core, and PLA-based multi-cell structures with varying geometries, including circular, square, and hexagonal shapes. These components were fabricated through 3D printing and subjected to quasi-static axial compression testing. The experimental findings indicate that incorporating a hybrid core significantly enhances energy absorption capabilities. Among the tested configurations, the hexagonal multi-cell design exhibited the highest energy absorption, reaching 0.53 kJ. In addition, the CB-Al-H configuration, which uses an Al core, showed the highest specific energy absorption (SEA) of 77.77 kJ/kg and a crushing force efficiency (CFE) of 0.43%. This SEA value is approximately 69.17% higher than that of the copper-based configuration (CB-Cu-H), which recorded 45.98 kJ/kg with a CFE of 0.48%. The lower SEA observed in the copper-core configuration is primarily due to the higher Cu density, which increases the overall structural mass and consequently reduces specific energy absorption.